Mindfulness in stress management for college students (Research, Society and Development, 2020)
Objective: The study aims to describe the content covered in scientific productions on the theme Mindfulness in the management of stress for university students. Methodology: An integrative literature review was carried out in the LILACS, PUBMED and MEDLINE databases, using the keywords "mindfulness", "mindfulness", "students" "stress" and "anxiety", selecting articles in English and Portuguese from last five years (2014 to 2019), with full text and available online. Results: From the analysis of the 51 publications found, two categories were developed: 1. The management of stress and the benefits of its practice, subdivided into Mindfulness as a learning tool and The promotion of self-acceptance and the acceptance of the other; 2. Difficulties to practice mindfulness. Conclusion: The use of mindfulness as stress management in university students has been considered an effective strategy in reducing the stress caused by academic life, in addition to providing improvement in health problems and academic performance.